Mesh generation and blood flow simulation in human carotid bifurcation - C. F. Castro (2012)
The ability to associate blood flow features with parameters representative of the vessel geometry is fundamental to perform studies that might help surgeons understand the development of artery diseases. A tool to generate structured computational meshes for vascular modeling frameworks and a three dimensional finite element model for blood flow simulation is presented here. Blood flow is described by the incompressible Navier-Stokes equations and the simulation is carried out under pulsatile conditions. Results of patient-specific reconstruction with structured meshing of the left carotid bifurcation using Doppler ultrasound images together with blood flow simulations demonstrate the performance of the developed methodology. (c) Civil-Comp Press, 2012.